Transforming the Teaching of Arabic Writing Skills through the Think Pair Share Strategy - Rahmah Fadhilah Agustina; M. Syihabul Ihsan Al Haqiqy (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
riting instruction in Arabic often faces various challenges, such as low student motivation, limited vocabulary, and a lack of ability to develop ideas in written form. These conditions make the learning process less effective and result in suboptimal student writing performance. Therefore, it is necessary to apply a cooperative learning strategy such as Think-Pair-Share as an alternative to enhance students’ participation and writing skills through collaboration. The purpose of this study is to describe the implementation of the Think-Pair-Share strategy in teaching maharah al-kitābah (writing skills). The subjects of this study were eighth grade students of State Islamic Junior High School of Batu. Data collection techniques included observation, unstructured interviews with ten students, and documentation related to the main Arabic textbook. The data analysis technique employed the flow model of Miles, Huberman, and Saldana, which consists of data condensation, data display, and verification. The results of the study show that the use of the Think-Pair-Share strategy in maharah al-kitābah consists of five steps: (1) Introduction, the teacher divides students into several groups; (2) Think, students answer questions individually and write them on worksheets; (3) Pair, students discuss their answers in groups and write the best group answer on the worksheet; (4) Share, students present the group’s work on the board, which is then commented on by other groups; and (5) Closing, the teacher provides feedback by clarifying, correcting, and concluding the correct answers from each group’s discussion. Thus, the use of this strategy not only emphasizes the collaborative aspect but also integrates critical thinking and individual reflection processes before writing.